Various production and service models on small-scale of natural products as a new job opportunity for pharmacists. - Bagheri, Sara; Azadi, Amir; Ashrafi, Hajar; Razmjou, M.Mahdi; Zare, Marziyeh; Abolhassanzade, Zohre; zarshenas, M.Mahdi; Badr, Parmis; Mohagheghzade, Abdolali (International Pharmacy Acta, 2018)
Introduction: pharmacists’ job opportunities in Iran are limited to the presence in the industry, pharmacy, hospital, research-centers and faculty of universities. The need of our community to the pharmacist is quantitatively 32 pharmacists per 100,000 people. Every year, 1000 pharmacists graduate in Iran; but there are not enough adequate employment opportunities for them. Given the huge costs of establishing and purchasing a pharmacy and a factory. Job opportunity for pharmacists should be created based on entrepreneurship principles. These opportunities can be defined in the format of designing knowledge-based models that are managed by the pharmacist. There are remarkable amounts of natural products required by healthcare providers on a small scale every day. Manufacturing these products is not cost-effective for a large industrial complex. Small-median enterprises model is one of the reasons for the success of the BRICK countries based on the small-scale chain production ultimately make a huge economic network structure with high profitability. Methods and Results: Regulations of Health Ministry, the GMP principles for herbal productions, regulations of nutrition supplements registration, the process of issuing the production license, the process of issuing the establishment permit, the minimum requirements for establishing the units of medicinal plants packaging and production of plant extracts, the regulation for getting packaging and production license for plant products,supportive-policy package, industry relations with the university in the area of food and drug, regulations and guidelines for registration and establishment of knowledge-based companies, all were investigated.According to the existing criteria, the following proposed models can be presented:1) Small production with maximum 10 employees; including solids, semisolid and liquids production departments.2)Production workshop model outside the city with maximum 50 employees. 3) Providing consultation and training services in the field of medicine. Conclusions: As the pharmaceutical community need to the job that by applying a not-so-great capital to have a proper efficiency, and the pharmacist to use his knowledge, a set of products as a network can besides providing these needed items, provide the country with natural products. Therefore, the facilities to create new pharmaceutical job opportunity as well as holding empowerment courses for pharmaceutical students in this field are required.